Karakalpak Language In The Words Phonological Structure - Zarip Yaqyaev (International Scientific and Current Research Conferences, 2021)
This article examines the phonological changes in morphemes of borrowings of the Karakalpak language. Study shows of the process of penetration of elements of one language into another. Researchers examined some works and prove that the facts about the transformation of foreign language elements exit in Karakalpak.